2011
DOI: 10.18388/abp.2011_2292
|View full text |Cite
|
Sign up to set email alerts
|

Association between estrogen receptor alpha gene polymorphisms and bone mineral density in Polish female patients with Graves' disease.

Abstract: Graves' (GD) hyperthyroidism leads to reduced bone mineral density (BMD) accompanied by accelerated bone turnover. Ample studies have identified association between estrogen receptor (ESR1) gene polymorphism and decreased BMD and osteoporosis. In contrast, number of publications that link ESR1, BMD and Graves' disease is limited. The purpose of this study was to identify the association between ESR1 polymorphisms and BMD in premenopausal women with GD and to determine whether ESR1 polymorphic variants can pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…They found that in premenopausal women with GD, homozygous for xx of Xba I (AA) and pp of Pvu II (TT) had the lowest BMD at the lumbar spine. Moreover, the px haplotype was predisposed to reduced lumbar spine BMD [55].…”
Section: Discussionmentioning
confidence: 99%
“…They found that in premenopausal women with GD, homozygous for xx of Xba I (AA) and pp of Pvu II (TT) had the lowest BMD at the lumbar spine. Moreover, the px haplotype was predisposed to reduced lumbar spine BMD [55].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have determined that the single nucleotide polymorphisms (SNPs) of ESRα might be related to many disorders, including osteoporosis [19], stroke [20], and Alzheimer’s disease [21]. Interestingly, other studies have indicated that the SNPs in ESRα are also associated with many psychiatric disorders.…”
Section: Introductionmentioning
confidence: 99%